Distributed Practice in Math Facts Fluency: A Comparative Analysis of Varied Intersession Intervals. Issue 5 (11th October 2022) - Powell, Steven L.; Duhon, Gary; Poncy, Brian C.; Mwavita, Mwarumba; Englen, Alexander J. N.
Abstract: We examined the math facts fluency growth of students receiving explicit timing practice in either a massed, short-distributed, or long-distributed fashion. In a repeated measures group design, 43 Midwestern third-grade students completed four 1-min math probes each day for 20 days. Hierarchical linear modeling revealed that students who received practice separated by a 3-hr interval grew significantly more than students who practiced with a 10-min distribution or a massed presentation. Impact Statement Our study found further support that separating math fact fluency practice by an interval of at least 3 hr leads to greater learning than practicing for the same amount of overall time but without separating the practice.